PENGGUNAAN INFORMASI AKUNTANSI DALAM PENENTUAN STRATEGI UMKM DI ERA KENORMALAN BARU - Anastasia Susty Ambarriani Sunaryo; Ch Wiwik Sunarni; Pratiwi Budiharta (Center for Economic Studies Universitas Katolik Parahyangan, 2023)
The covid-19 pandemic that occurred more than a year ago has affected many businesses, including micro, small and medium enterprises (MSME). The focus of this study is to describe the effect of the pandemic on the business of micro, small and medium enterprises located in Daerah Istimewa Yogyakarta, Indonesia. The study investigates the strategies taken by MSME in coping with challenges of the pandemic and how MSMEs use accounting information in their routine business operation. Data for analysis were gathered by means of questionnaires distributed to owners and or managers of MSME in the Daerah Istimewa Yogyakarta Province. Based on the respondents’ answers, the pandemic has caused a decline is sales, difficulty in recovery of operating costs, and difficulty in financing. The strategy taken by most MSMEs to counter those problems were rescheduling production, changing marketing techniques such as using online marketing, and increasing the quantity and quality of customer relationship. During the pandemic, respondents have realized the usefulness of accounting information in operating the business. Respondents know the importance of recording transactions which leads to a better calculation of costs and profit.